PELATIHAN ASSERTIVE DAN PERILAKU CYBERBULLYING PADA SISWA SMA DI SIDOARJO - Irmayanti, Nur (Jurnal Psikologi : Media Ilmiah Psikologi, 2020)
The long-term goal of this research is to try to reduce the cyberbullying problem lane in Indonesia, as it is known that the victims of cyberbullying cases are increasing every year. one of the causes is the lack of assertiveness towards the victim and in order to be more prudent in using information technology. The solution to these problems is through socialization or training related to cyberbullying, namely socialization or assertive training. Whereas the specific target to be achieved is after assertive training in order to minimize cyberbullying victims and provide information to others. The cyberbullying variable in this study is an independent variable and the assertive training dependent variable. The population in this study was from class X students at MA Darul Ulum Sidoarjo, amounting to 90 students. The study will use a sampling method that is census, so that all populations will be given training and cyberbullying scale. The analysis technique that will be used is to use paired t-test analysis. With a significance result of 0,000 <0.05, then Ho is rejected and Ha is accepted, meaning that the hypothesis states that there are differences before and after being given assertive training in reducing cyberbullying behavior, meaning that with assertive training it decreases cyberbullying behavior